Importance of environmental settings for the temporal dynamics of creativity. (September 2021) - Daikoku, Tatsuya; Fang, Qi; Hamada, Tomohito; Handa, Youichi; Nagai, Yukie
Highlights: Temporal dynamics of cognitive processes are crucial in acquiring creative ideas Influence of environmental settings on temporal dynamics of creativity is unclear We aimed to elucidate the environmental settings that enhance cognitive performance The optimal environmental conditions vary depending on the temporal dynamics stages Abstract: Human creativity refers to the cognitive capacity to produce new and valuable information. Over a long period of time, many people have been fascinated by the question of how creativity emerges in our brain and how it can be enhanced. Recently, a growing number of studies have revealed that some types of environmental stimuli can enhance human creativity. Further, specific temporal dynamics of cognitive processes are crucial for generating creative ideas. However, how the temporal dynamics of creativity are influenced by the environment remains unclear. Through a literature review of neural and psychological research, this study aimed to elucidate the environmental settings that enhance cognitive performance. We found that each stage of the temporal dynamics of creativity may be differently correlated with neural function. Further, environmental factors may have various, and sometimes contrasting, effects on the temporal dynamics of creativity. We propose a hypothesis that the optimal environmental condition varies depending on the stages of temporal dynamics since each stage requires different cognitive processes. However, there is a need for future studies to elucidate how creativity is modulated by social conditions and the physical environment as well as whether there are differences in the ideal environment for individual and group creativity. Nonetheless, this is the first study to clarify the influence of environmental settings on the temporal dynamics of creativity from the perspective of neuroscience and psychology.